A systematic scoping review of tiger conservation in the Terai Arc Landscape and Himalayas. Issue 6 (2nd November 2022) - Yadav, Pramod K.; Brownlee, Matthew T. J.; Kapoor, Mohnish
Abstract: In the last decade the tiger Panthera tigris population in the Terai Arc Landscape and Himalayas has increased, while populations in other countries have remained below their conservation targets. Although there has been some research on tiger conservation in the Terai Arc Landscape and the Himalayas, scientists and managers have not catalogued and characterized tiger research in the region, with empirical findings scattered among disparate document types, journals and countries. Without a review of the tiger research in the Terai Arc Landscape and Himalayan region, it is difficult to analyse or change conservation policies, develop adaptation strategies, prioritize research, allocate resources or develop conservation strategies potentially employable elsewhere. We therefore conducted a systematic scoping review to identify focal research areas, the spatial and temporal distribution of study sites, general publication trends, the extent of empirical studies, and gaps in tiger conservation research in this region (which spans Bhutan, India and Nepal). Since 2000, 216 studies have been published on issues associated with tiger conservation in the Terai Arc Landscape and Himalayas, with an increasing number over time. Most empirical studies have focused on tiger habitat, ecology and conflicts in protected areas in the region's foothills. There are research gaps in high-altitude landscapes, social science investigations, conservation economics, and policy and institutional analyses.